The Third Sustainable Development Goal: End Epidemics and other Communicable Diseases; Indian Perspective - Salam, Anas Abdul; Hiremath, Shobha Rani R.; Iram, Mahvash (Indian Journal of Pharmacy Practice)
Developing countries are the one who suffers the major and in-depth consequences of most of the infectious and epidemic diseases. The consequences includes, high rate of mortality, long term disability, and significant socioeconomic uncertainty. In India, the range and burden of infectious diseases are enormous. There is huge gap between surveillance and response system for infectious diseases in India. Maintaining personal and environmental hygiene is one of the major recommendations, but this requires a high quality in infrastructure and living of the people. The sustainable development goals make a bold commitment to end the epidemics of AIDS, tuberculosis, malaria and other communicable diseases by 2030. The aim is to achieve universal health coverage, and provide access to safe and effective medicines and vaccines for all. Experience has shown that the risk of disease outbreaks and deaths might be minimised through early introduction of disease surveillance, epidemic preparedness, effective prevention and control including case management.
Keywords: Epidemics; SDGs; Strategies; AIDS; TB